Characterization of Gambierdiscus and Coolia (Dinophyceae) isolates from Thailand based on morphology and phylogeny. Issue 2 (21st November 2014) - Tawong, Wittaya; Nishimura, Tomohiro; Sakanari, Hiroshi; Sato, Shinya; Yamaguchi, Haruo; Adachi, Masao
Summary: The benthic dinoflagellates in the genus Gambierdiscus produce toxins that bioaccumulate in tropical and sub‐tropical fish causing ciguatera fish poisoning (CFP). Other co‐occurring genera such as Coolia have also been implicated in causing CFP. Little is known about the diversity of the two genera Gambierdiscus and Coolia along the Thai coasts. The results of morphological analyses based on observation under light microscopy and scanning electron microcopy showed that strains of Gambierdiscus from Thailand displayed the typical Gambierdiscus plate formula: Po, 4′, 0a, 6″, 6c, ?s, 5′′′, 0p and 2′′′′. Morphological examination of Thai Gambierdiscus enabled it to be identified as Gambierdiscus caribaeus : round and anterior‐posteriorly compressed cell shape, broad 2′′′′ plate, rectangular 2′ plate, and symmetrical 3″ plate. The phylogenetic analyses based on the large subunit (LSU) rDNA D8/D10 sequences of Gambierdiscus from Thailand confirmed the morphological identification. The thecal plate formula for all of the Coolia isolates from Thailand was Po, 4′, 0a, 6″, ?c, ?s, 5′′′, 0p and 2′′′′. Most, but not all, of these isolates could be identified morphologically as Coolia malayensis . An LSU rDNA D1/D2 phylogenetic analysis confirmed identity of C. malayensis isolates identified morphologically. The remaining unidentified isolates fell in the C. tropicalis clade.